Energy and spectral efficiencies of cell-free millimeter-wave massive mimo systems under rain attenuation based on ray tracing simulations - Silva, Higo Thaian Pereira da (2023)
Future wireless communication systems depend on the network’s ultra-densification, on the application of massive multiple-input multiple-output (mMIMO) techniques and on the use of higher frequency bands to satisfy the ever-increasing demands for capacity. The operation of cell-free (CF) networks in the millimeter wave (mmWave) spectrum combines those principles, because they are composed of multiple access points (APs) distributed over a geographic region which serve a small number of users. Despite the extensive available bandwidth, the mmWave spectrum imposes high path losses and significant atmospheric molecular absorption to the links. In addition, in this frequency range, rain attenuation can notably degrade communications. Therefore, this article presents a study of the impact of rain attenuation on CF networks operating in the mmWave spectrum, this is in the 26 GHz, 38 GHz and 73 GHz frequency bands, based on site-specific ray tracing simulations. The propagation simulation is characterized under the effects of reflection, diffraction, diffuse scattering, atmospheric molecular absorption, vegetation losses and rain attenuation. The channel model is characterized using a hybrid approach, with the large-scale parameters determined by ray tracing in an environment subject to random Rician small-scale fading. The system performance is measured by the sum spectral efficiency (SSE) and energy efficiency (EE). According to the results, it was observed that AP densification protects the network against the effect of rain attenuation. Furthermore, even in sparse networks, the CF system has low sensitivity with respect to the precipitation rate, resulting in relatively small reductions in the average SSE and EE.